Mathematical modelling of brain bioelectricity: an insightful tutorial. (2016) - Abouelseoud, Gehan; Ismail, Nour; Shoukry, Amin; Mekky, Jaidaa
Mathematical modelling of brain bioelectricity is important for different applications ranging from medicine to engineering sciences. This tutorial aims to offer a global view of available modelling approaches and their suitability for different applications. It is written in a way that is intended to equally help engineers (with low biology background) and medical practitioners (with low mathematical background) in getting a quick grasp of the subject. Although, the tutorial focuses on brain bioelectricity, reading it can give insight into basic concepts which are essential for the mathematical modelling of any biological process in general.